A DESCRIPTIVE STUDY OF CODE MIXING PHENOMENON IN “BRIDEZILLA” MOVIE - Yuli Fatmawati; Wulan Wangi; Wageyono (LUNAR, 2022)
Code mixing in movie is the phenomenon found in almost our daily life. The characters use two or more languages into one phrase to make communication with the interlocutor. When, someone communication could be more interesting mix the languages. The reseacher analysed Bridezilla movie to identify the types of code mixing and to describe the factors of code mixing. The types and factors of code mixing are based on Fasold and Weinrich theory. The result showed that Bridezilla movie consist two types (word and phrase type). The result showed that there are 73 words and 48 phrases type. The dominant type of code mixing is “word”. The researcher found that there are factors of code mixing, they are 105 internal factors (8 homonyms, 95 low frequencies of word, and 2 synonyms) and 16 external factors (4 factors of introduction and development of new cultures, 3 factors of oversights, and 9 factors of social values). Based on the result above, it was concluded that all types and factors of code mixing that was found in Bridezilla movie.